Knowledge and attitude towards patient safety among registered nurses of a private hospital in Selangor Malaysia - Norhayati Jamal; Aini Ahmad; Annamma Kunjukunju (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Many patients experience losses during hospitalization due to various mistakes and unwanted events. Knowledge and attitudes of nurses toward patient safety greatly affect the provision of safe patient care. Registered nurses need good knowledge and attitudes to provide good nursing care during inpatient care.Purpose: To improve the knowledge and attitude of registered nurses toward patient safety with proper guidelines to prevent any incident or adverse event and simultaneously improve safety and quality health care in Malaysia.Method: This cross-sectional analytic study was conducted in 2021 at a private hospital in Klang Valley, Malaysia. One hundred twenty-eight (128) registered nurses (RNs) were recruited through non-probability sampling. This questionnaire was used to collect data, which was then analyzed using SPSS Version 26, descriptive analysis, Kruskal Wallis, and Mann-Whitney tests.Results: Showed that 124 respondents (96.9%) had good knowledge about patient safety, and 47.7% (61 respondents) had a good attitude. The relationship between nurses' knowledge of patient safety and age, education level, experience, and unit or department was not significant at p values 0.362, 0.902, 0.466, and 0.307, respectively.Conclusion: Determining the knowledge and attitudes of nurses toward patient safety will improve the quality of nursing care by preventing incidents that are detrimental to patients.